What makes a problem complex?: Factors determining difficulty in dynamic situations and implications for diagnosing complex problem solving competence - Greiff, Samuel; Funke, Joachim (Beyond knowledge: the legacy of competence, 2008)
Complex problem solving within dynamic systems has been an area of major interest in experimental research over the last decades.